Academic nurse leaders' interpretation of concepts and priorities related to the examination of scientific short papers, dissertations and theses - Part 2 - H. Brink (AOSIS, 1993)
During the first round of the study panel members were asked to comment on the kinds of evaluation instruments they considered appropriate. The responses did not indicate clearly their preferences except that no one was in favour of a detailed evaluation instrument which indicated weights for each criterion.